Comparison of musculoskeletal disorder health claims between construction floor layers and a general working population. Issue 1 (15th September 2014) - Dale, Ann Marie; Ryan, Daniel; Welch, Laura; Olsen, Margaret A; Buchholz, Bryan; Evanoff, Bradley
Abstract : Objectives: Compare rates of medical insurance claims for musculoskeletal disorders (MSD) between workers in a construction trade and a general worker population to determine if higher physical exposures in construction lead to higher rates of claims on personal medical insurance. Methods: Health insurance claims between 2006 and 2010 from floor layers were frequency matched by age, gender, eligibility time and geographic location to claims from insured workers in general industry obtained from MarketScan. We extracted MSD claims and dates of service from six regions of the body: neck, low back, knee, lower extremity, shoulder and distal arm, and evaluated differences in claim rates. Results: Fifty-one per cent of floor layers (n=1475) experienced musculoskeletal claims compared with 39% of MarketScan members (p<0.001). Claim rates were higher for floor layers across all body regions with nearly double the rate ratios for the knee and neck regions (RR 2.10 and 2.07). The excess risk was greatest for the neck and low back regions; younger workers had disproportionately higher rates in the knee, neck, low back and distal arm. A larger proportion of floor layers (22%) filed MSD claims in more than one body region compared with general workers (10%; p<0.001). Conclusions: Floor layers have markedly higher rates of MSD claims compared with a general worker population, suggesting a shifting of medical costs for work-related MSD to personal health insurance. The occurrence of disorders in multiple body regions and among the youngest workers highlights the need for improved work methods and tools for construction workers.